THE MYSTERY OF THE ARMENIANS MISSION - ZAKARYAN, SEYRAN (Bulletin of Yerevan University E: Philosophy, Psychology, 2019)
From the second half of the XIX century in Armenian Social Science thought an idea/myth was formed on Armenian nation mission, according to which Armenians, being a nation that acquires and carries European values, is called to be a "light lamp", "civilization builder", "Champion of the Westernism" for Asia "buried in darkness". The defenders of this idea relied on the fact that Armenians have demonstrated their intellectual and practical abilities at all stages of history, culture and civilization and have played a prominent role in the countries where they lived and contributed to the military, state, political and cultural life development. One of the primary goals of the missionary idea for being a "light lamp" for Asia was to: (a) to convey the self-assertion to an awakening nation, which later went through massacres and became desperate, (b) to draw the attention of European states to the national liberation struggle of Armenians. The nominees of this mythologema claimed that the Armenian nation, being an ancient civilization and a nation of Christian and European values, was in a difficult situation and expect moral and military-political assistance from its "native" Europe. According to the author’s opinion, the Armenian missionary idea had a mythical nature, because Armenians, though highly civilized compared to their neighboring nations, had no power, no means or opportunities to "illuminate" their neighboring tribes, who looted and humiliated Armenians for centuries. The Armenians were in such a state that first of all they had to think about maintaining their physical existence, then to "enlighten" and "civilize" them. If the Armenian nation had and has any mission or duty to humankind, it was not to serve others, not to transmit the achievements of one civilization to another, but first of all, enriching its civilizational capital with both Western and Eastern values, preservation of its cultural uniqueness and modernization in line with the spirit of the current times.